Formulasi Strategi Diniyyah Training Center (DTC) Pondok Pesantren Perguruan Diniyyah Puteri Padang dalam Meningkatkan Kinerja Karyawan - Risham, Muhammad Nabil; Azis, Ali; Hamdani, Amin (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to examine: (1) the process of setting direction and objectives; (2) analysis of the internal and external environment; (3) strategic steps taken to achieve measurable and sustainable performance improvements. The method used is a case study with a qualitative approach. The theory used refers to the concept of strategy formulation according to David and performance indicators according to. The results of the study indicate that strategy formulation at DTC is carried out in a participatory manner, involving leaders and training staff. The institution's vision and mission form the basis for developing training programs that are not only oriented towards improving technical competencies, but also strengthening Islamic character values. SWOT analysis is used to design strategies that are adaptive to internal strengths and external challenges. Strategic steps such as routine training, mentoring, periodic evaluations.